From Humans to Androids to Holograms: the Persistence of Character in Star Trek: The Next Generation and Voyager - Isabelle ROBLIN (E-REA)
Over the years, posthuman, AI-based characters have become fairly common in the Star Trek franchise, and the very question of their ontological status and of their relationship with the various human, humanoid or alien crews they work with is explored and evolves within the different series. My contention here is that this questioning can be seen as a mise en abyme of the concept of character in a posthumanist culture and lead to “a renewed interrogation of character” (Anderson, Felski and Moi 14). I shall concentrate on two of these main recurrent “characters,” the android officer Lt. Commander Data in The Next Generation and the holographic Doctor in Voyager. After a brief examination of some of the most thought-provoking societal and ethical issues dealt with in the franchise from its very beginning through human characters such as Lieutenant Uhura in the original series, I shall analyse how, from the late 1980s, with the rapid spread of AI in all fields of society, non- humanoid characters like Data and then the Doctor have incarnated (so to speak!) the passionate debate notably in posthumanism studies about “the measure of a character,” a take on the title of one of the most famous episodes of The Next Generation.